Study on optimization of solidifying agent proportions and performances of fluid solidified soil based on vibration mixing - Kai Wang; Yunshi Yao; Jianhui Niu; Wenjie Yang; Shibin Chen (Materials Research Express, 2025)
Fluid solidified soil is a new type of backfill material in construction pits, fertilizer troughs, and mining goafs. However, its economic, workability, and mechanical properties are important factors that restrict its widespread application. In this paper, based on a traditional cement solidifying agent, the effects of a two-component solidifying agent and vibration mixing process on the properties of fluid solidified soil are studied. By adding industrial slag, solidifying agents A (cement), B (cement and CFB ash), C (cement and blast furnace slag), and D (cement and steel slag) were prepared using normal mixing and vibration mixing, and the workability and mechanical properties of the solidified soil were tested. Experimental studies have shown that, with an 8% reduction in the proportion of solidifying agent and soil solidifying agents, the expansion degree, stone formation rate, and 7-day strength of fluid solidified soil are comparable to those with a cement solidifying agent. Compared with the performances of four types (A, B, C and D solidifying agents) of solidified soil under normal mixing, their 28 d compressive strength under vibration mixing increased by 8.5%, 11.0%, 15.1%, and 9.8% respectively, and their water stability under vibration mixing increased by 17.6%, 9.6%, 17.7%, and 20.0% respectively. The results have shown that using two-component solidifying agent and reducing the amount of cement can produce solidifying agents that are equivalent in performance to cement. Moreover, vibration mixing can improve the mechanical properties of solidified soil for different solidifying agents. This study provides an engineering foundation for the widespread application of fluid solidified soil.